HEAVY METAL Pb CONTENT IN THE SEAWATER, SEDIMENT AND GREEN MUSSEL TISSUE Perna viridis - M. Gandri Haryono; . Mulyanto; Yuni Kilawati (Department of Marine Science and Technology, Faculty of Fisheries and Marine Science, IPB University, 2017)
Accumulation of heavy metal Pb into the tissue can proceed through a food chain or environmental exposure. This study was to determine the content of heavy metals Pb in water, sediments and mussels (perna viridis). This research was conducted in March 2016, in the waters of Lekok Pasuruan at the three stations. TPI Station 1, Station 2 at the mouth of the Rejoso river and station 3 nearby PLTU 3. The water, sediments and green mussels (Perna viridis) samples were collected for Pb analysis using Absorpotion Atomic Spectrophotometer (AAS). In addition to the water quality such as salinity, temperature, DO and pH was observed. The results showed the highest Pb content in the water (0.4444 mg/l), sediment (23.8284 mg/kg) and green mussel tissue (1.5098 mg/kg) were found at station 2 (Rejoso river mouth). The Pb content in green mussel seemed to above safety level to consume.